EDUKASI DAN PENERAPAN JUAL BELI DALAM HUKUM ISLAM BAGI SISWA/SISWI SMP PEMBANGUNAN LABORATORIUM UNP PADANG - Fadhli, Ashabul; Devi Syukri Azhari; Usman, (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2025)
This study aims to provide education and observe the application of Islamic principles of buying and selling among students of SMP Pembangunan Laboratorium UNP Padang. In today’s modern era, buying and selling have become a daily activity, including in the school environment. However, many students still lack understanding of the Islamic values embedded in trade transactions, such as honesty, fairness, and the requirement of halal goods. Therefore, this educational activity was carried out through lectures, interactive discussions, and simulation of simple trading practices.The results showed a significant improvement in students’ understanding of Islamic concepts of buying and selling. Students were able to explain the pillars and conditions of Islamic trade and recognize prohibitions such as riba (usury) and deception. In practice, they began to apply these principles in their daily activities. This program proved effective in instilling Islamic commercial ethics from an early age and in shaping students' religious character in economic interactions.